What will this do to me and my brain? Ethical issues in brain-to-brain interfacing - Hildt, Elisabeth (Frontiers in Systems Neuroscience, 2015)
For several years now, brain-computer interfaces (BCIs) in which brain signals are used to navigate a computer, a prostheses or a technical device, have been developed in various experimental contexts (Wolpaw & Wolpaw 2012; Grübler & Hildt 2014). Researchers have recently taken the next step and run experiments based on connections between two brains. These so-called brain-to-brain interfaces (abbreviation: BBIs or BTBIs) involve not only a BCI component deriving information from a brain and sending it to a computer, but also a computer-brain interface (CBI) component delivering information to another brain. What results is technology-mediated brain-to-brain communication (B2B communication), i.e. direct communication between two brains that does not involve any activity of the peripheral nervous system. In what follows, ethical issues that arise in neural interfacing will be discussed after a short introduction to recent BBI experiments. In this, the focus will be on the implications BBIs may have on the individual at the CBI side of the BBI, i.e. on the recipient.